Rasionalitas Skala Prioritas Ekonomi Perempuan Penganyam Ketupat di Desa Joanyar Buleleng - Indrayani, Luh; Ni Wayan Ayu Santi (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
This research aims to determine the meaning of the rationality of the economic priority scale of women ketupat weavers in Joanyar Village, Buleleng. Each individual in the family tries to provide the necessities to maintain survival. Unlimited human needs and the many choices with limited means of satisfying needs require humans to have a rational attitude in determining various needs choices. Be rational in making choices that suit your life needs to avoid consumptive nature. The needs priority scale helps individuals make the best choice for themselves. This is interesting to study considering how complex the provision of needs is for each person. Qualitative method with a grounded research approach to explore social processes that occur in human interactions. Data was collected through interviews and observations with 10 informants regarding the rationality of the economic priority scale. The results of the research show that female ketupat weavers have reasons for determining the priority scale of needs, which are important and urgent in quadrant I.